UPAYA MENINGKATKAN MOTIVASI BELAJAR SISWA PADA PEMBELAJARAN DARING DI SMA NEGERI 2 KAMPAR - Ardianti; Bakti, Faisal; Hambali; Sopiar (PGRI Provinsi Riau, 2021)
The purpose of this research was to determine the role of teacher competence in shaping student learning motivation through online learning at SMAN 2 Kampar.To obtain data, facts and information that will reveal and explain problems, researchers use a descriptive approach. The data and instruments in this study are primary data. The data collection instruments were observation, documentation and interviews. As for the comparisons we can get from previous research that is relevant to the title of this study is the lack of ways teachers develop interest in learning at SMA N 2 Kampar by giving gifts, making approaches, encouraging learning, directing learning activities and giving praise to students. So it can be concluded that in shaping student learning motivation cannot be implemented by teachers based on their competencies, this is because the learning system is carried out online.